Atopy and autoimmune thyroid diseases: melatonin can be useful?. Issue 1 (December 2016) - D'Angelo, Gabriella; Marseglia, Lucia; Manti, Sara; Colavita, Laura; Cuppari, Caterina; Impellizzeri, Pietro; Arena, Salvatore; Arrigo, Teresa; Salpietro, Carmelo; Gitto, Eloisa
Abstract Recently, there has been growing interest in the relationship between allergic and autoimmune diseases. Allergy and autoimmunity can be considered two potential outcomes of dysregulated immunity and analysis of literature data shows a strong positive association between a history of Th2-mediated allergic disorders and Th1-mediated autoimmune disorders. Autoimmune thyroid diseases are the most common of all autoimmune pathological conditions. Currently, the mechanisms explaining an association among atopy, autoimmunity, and thyroid diseases are not fully understood. There are data in literature pointing to the relationship between melatonin and thyroid activity. Several studies have suggested a paracrine role for this molecule in the regulation of thyroid activity, documenting that administration, as an antioxidant, in thyroid tissues under conditions of increased oxidative stress, could be helpful to reduce the oxidative processes involved in autoimmune thyroid diseases. Although thyroid autoimmunity has been regularly associated with atopic conditions in children, the possible protective role of melatonin has not yet been investigated. This review summarizes what is known regarding the connection between atopy and autoimmune thyroid diseases, and analyses the probable beneficial action of melatonin.